Short‐flap facelift with 924 nm/975 nm laser lipolysis: a retrospective study of 78 patients. (March 2014) - Ramirez, Patrick; Leibowitz, Alicia; Traylor‐Knowles, Mimi; Taghizadeh, Farhan
Summary Objectives This study reviews the overall outcome of 78 patients undergoing a short‐flap facelift with laser‐assisted lipolysis using a continuous‐wave 924/975‐nm diode laser. Methods Seventy‐eight patients undergo treatment of lipolysis and facelift using the traditional platysmaplasty technique along with continuous‐wave 924/975‐nm diode laser‐assisted lipolysis. A combination of 3D and 2D photographs is used from before, 6 weeks after, and 6 months after the procedure to judge the overall improvement in the cervicomental angle and the patient's general appearance. The Cervicomental Scale and the Global Aesthetic Improvement Scale Assessments, respectively, are used among a professional panel of three judges to determine improvement. Results Elevated flap, continuous‐wave lipolysis showed remarkable improvement in patients base on the CAS and GAIS judging system. Ninety‐five percent of patients showed improvement on CAS and 100% of patients showed improvement on GAIS when 6 months had passed after time of procedure. Conclusion The use of a continuous‐wave 924/975‐nm diode laser shows remarkable effectiveness in lipolysis of the sensitive jowl and neck area. Flap elevation serves as an important technique in assuring safety during procedure. This dual‐wavelength laser presents a revolutionary advance in performing facelifts and lipolysis in higher BMI patients.